2017
DOI: 10.1007/s40292-017-0201-8
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of High Blood Pressure Prevalence, Awareness and Control in the Italian General Population

Abstract: Our data suggest that BP control could be achieved by 2020, as recommended by WHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…During past decade, there was no increasing trend of SBP and DBP levels in America 11 , 12 during the past two decades and in Japan 13 , while there was a consistent decreasing of BP in Germany 14 , Spain 15 , Italy 16 and Korean 17 . From 1988 to 2008, there was an increasing trend of hypertension prevalence in Americans aged 40 years and older 11 , however, the prevalence of hypertension in Japan 13 , Germany 14 , Italy 16 and Korea 17 decreased. Other Chinese studies in other areas 18 20 also have found that there is an increasing trend of prehypertension and hypertension prevalence.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…During past decade, there was no increasing trend of SBP and DBP levels in America 11 , 12 during the past two decades and in Japan 13 , while there was a consistent decreasing of BP in Germany 14 , Spain 15 , Italy 16 and Korean 17 . From 1988 to 2008, there was an increasing trend of hypertension prevalence in Americans aged 40 years and older 11 , however, the prevalence of hypertension in Japan 13 , Germany 14 , Italy 16 and Korea 17 decreased. Other Chinese studies in other areas 18 20 also have found that there is an increasing trend of prehypertension and hypertension prevalence.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless the treatment in Chengdu is unluckily lower than in Shandong 18 , Beijing 19 , while higher than in Chongqing 20 , India 21 and Thailand 22 . In past decade, the hypertension control doubled in Germany 14 , Spain 15 and nearly doubled in America 11 and it increased steadily in developed couriers, such as Italy 16 and Korean 17 . Unfortunately, the hypertension control in Chengdu was low, which was in accordance with studies in other Chinese cities 5 , 18 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension was reported to the most prominent cardiometabolic risk factors among the Chinese 33 34. From 1988 to 2008, there was an increasing trend of prevalence of hypertension in Americans aged 40 years and older,35 however, the prevalence of hypertension in Japan,36 Germany,37 Italy38 and Korea39 decreased. In our study, we found a significant decline in the prevalence trend for hypertension among Chinese adults in 2017 compared with 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of high blood pressure and cardiovascular prevention, Di Lonardo and colleagues [15] reported an updated analysis of this large database, which included data from three large epidemiological surveys: the risk factors and life expectancy (RIFLE) study [16], the Osservatorio Epidemiologico Cardiovascolare (OEC) [17] and the Osservatorio Epidemiologico Cardiovascolare/Health Examination Surveys (OEC/HES) [18]. What is relevant from this analysis is the very long observational period, which covered three main intervals (which covered 1978-1987, 1998-2002 and 2008-2012 periods, respectively), as well as the large population sample (which included about 70,000, 9712 and 9111 adult individuals, respectively).…”
mentioning
confidence: 99%